2013
DOI: 10.1007/bf03341674
|View full text |Cite
|
Sign up to set email alerts
|

Off to the Right Start: A Model for Developing Collaboration with Nurses Early in Medical School

Abstract: Purpose: Effective collaboration between physicians and nurses has been shown to enhance patient care, decrease errors, and reduce expenses related to inefficiency. The current study provides a qualitative analysis of student responses to an exposure-based interprofessional training model implemented at the University of Vermont. Method: First-year medical students (N = 99) participated in a one-on-one shadowing experience with inpatient nurses, shared training perspectives with nursing students, and composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…In our project, we found that the shadowing experience improved IPESAT scores and the morale and confidence of residents during chronic wound management, as reflected by their comments following the experience. While all 4 IPESAT domain scores improved statistically significantly, the greatest gain was in the domain of teamwork (10.8% increase), which mirrored other IPE studies 16,19,35. Moreover, resident comments reflected increased respect for other healthcare professionals, the CWOCN, a consistent finding with prior IPE programs 36…”
Section: Discussionsupporting
confidence: 57%
“…In our project, we found that the shadowing experience improved IPESAT scores and the morale and confidence of residents during chronic wound management, as reflected by their comments following the experience. While all 4 IPESAT domain scores improved statistically significantly, the greatest gain was in the domain of teamwork (10.8% increase), which mirrored other IPE studies 16,19,35. Moreover, resident comments reflected increased respect for other healthcare professionals, the CWOCN, a consistent finding with prior IPE programs 36…”
Section: Discussionsupporting
confidence: 57%
“…The present study goes beyond prior research on interprofessional shadowing demonstrating improvements in knowledge and attitudes (Fougner & Horntvedt 2011, Jain et al 2012, Wright et al 2012, Rosen et al 2013, Shafran et al 2015). It shows that shadowing can yield insights for preclinical students that many physicians do not gain until residency or beyond.…”
Section: Discussionmentioning
confidence: 79%
“…Shadowing can introduce students to the roles of other professionals (Fougner 2011, Wright 2012, Rosen 2013, Shafran 2015, Vasset 2015). Students also learn about communication and teamwork through shadowing activities (Fougner & Horntvedt 2011, Wright et al 2012, Rosen et al 2013). Additionally, shadowing can bring about attitudinal change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most IPE programs reported in the literature include passive lecture style teaching methods during pre-clerkship, and focus on student-to-student interactions from a range of health professions. 10 That being said, two published American studies from the University of Vermont 24 and the University of Michigan 25 were found, which outline innovative approaches to IPE similar to HEIGHTEN, whereby first-year medical students shadowed nurses. Both of these studies demonstrated positive interprofessional outcomes including enhanced knowledge of the nursing profession, an understanding of the importance of interprofessional communication, and improved medical student attitudes toward nurses.…”
Section: Discussionmentioning
confidence: 99%